How we have fallen: implicit trajectories in collective temporal thought. Issue 8 (14th September 2019) - Yamashiro, Jeremy K.; Roediger, Henry L.
ABSTRACT: Memory may play a critical role in the ability to imagine events in the future. While most work on this relation has concerned episodic memory and simulated episodic events in the future, the current study examines how collective memories relate to imagination for the collective future. Two thousand American participants provided events for (1) America's origins, (2) normative events that all Americans should remember, and (3) events in America's future. Each event was rated for emotional valence. Whereas collective memories – particularly origin events – showed pronounced positivity biases, there was a negativity bias in collective future thought, indicating an implicit trajectory of decline in Americans' representations of their nation across time. Imagination for the social future may not be simulated based on the template of collective memories, but may rather relate to the past in a way that is mediated by cultural narrative schemata.